P061 Safety of Single Dose Gentamicin Compared with Multiple Dose Regimens. (30th June 2016) - Hayward, Rachel; Harding, Jan; Molloy, Robert; Land, Lucy; Longcroft-Neal, Kate; Moore, Dave; Ross, Jonathan
Abstract : Background: Traditionally, gentamicin is given eight hourly, guided by drug levels. Several studies have shown that single-daily dosing of gentamicin offers an equal, if not improved, toxicity profile compared to traditional dosing. Single one-off dose gentamicin has been suggested as treatment for gonorrhoea, but its safety has not been reviewed. Aim: Systematically review the frequency and type of adverse events associated with a single dose of intravenous or intramuscular gentamicin in adults, for any indication, in studies where a comparator was available. Methods: A review protocol was developed and registered (PROSPERO: CRD42013003229). Studies were eligible for review if they; recruited participants ≥16 years old, used gentamicin intramuscularly or intravenously as a single one-off dose, compared gentamicin to another medication or placebo, and if adverse events were monitored. We searched MEDLINE, EMBASE and other relevant databases. Risk of bias was assessed in included studies. Results: 12, 116 records were identified. After removal of duplicates, screening of title/abstracts for relevance and independent selection of full texts by two reviewers, 20 studies were included. 3589 participants were analysed across all studies, 2042 received a single one-off dose of gentamicin (doses ranged from 1 mg/kg - 280 mg). Reversible nephrotoxicity/creatinine rise was reported in 37 cases, with one case of irreversible renal impairment. There were three cases of ototoxicity, with similar frequency reported in the comparator group. A meta-analysis was not possible due to heterogeneity. Reporting of adverse events was poor in the majority of studies. Discussion: Adverse events with single dose gentamicin are infrequent.